Religion and Spirituality in Addiction Recovery - Hahn, Jennifer Lois (Religion compass, 2025)
This article addresses the role of religion and spirituality in addiction recovery, the difficulties concomitant with studying this necessarily interdisciplinary subject, and the possibilities that an expanded understanding of addiction as a historical and cultural phenomenon offers. It provides an overview of the current state of alcoholism and addiction in the United States and globally, chronicling the ways in which alcohol and drug use and abuse has varied across time, cultures, and religious traditions. An overview of research on Alcoholics Anonymous (AA) reveals the need for studies informed by AA members' own understandings of spirituality and religion. The author suggests that tracing the historical development of the concept of addiction across cultures allows us to see how AA and other faith-based treatment programs act to ameliorate aspects of modern suffering sometimes ignored or undertreated by certain medical and psychological paradigms. An interdisciplinary dialog between mental health disciplines and the humanities and social sciences could expand the biopsychosocial model of addiction to include analysis of higher-order cultural and historical factors such as nationalism, political unrest, social isolation, economic ideology, and understandings of the nature of self. The author also calls for increased research on non-AA programs aiming to address addiction and alcoholism through religion and spirituality.